Performance study of the knockout switch subject to non-uniform traffic distribution - Tan, Kah Lung. (2008)
In this project, a computer model of the Knockout Switch is developed to validate the general model of the Knockout Switch under non-uniform traffic presented. Geometrically distributed, independent packets arrivals are generated at the switch inputs.